David Stowel and Elizabeth Stowel deeds - Stowel, David; Stowel, Elizabeth
Deeds for land owned by David Stowel and Elizabeth Stowel in Otsego County, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Deeds -- New York (State) -- Otsego County